Outcomes of Percutaneous Coronary Intervention in Patients with Spontaneous Coronary Artery Dissection - Saber Hassan; Rohit Samuel; Andrew Starovoytov; Carolyn Lee; Eve Aymong; Jacqueline Saw (Journal of Interventional Cardiology)
Objectives. To compare outcomes of percutaneous coronary intervention (PCI) in spontaneous coronary artery dissection (SCAD) patients versus conservative therapy. Background. SCAD is an important cause of myocardial infarction (MI) in young-to-middle-aged women. Percutaneous coronary intervention (PCI) is often pursued, but outcomes compared to conservative therapy are unclear. Methods. 403 nonatherosclerotic SCAD patients were enrolled between 2011 and 2017 and prospectively followed up in our Vancouver General Hospital registries. Detailed baseline, hospital, PCI, and outcomes were recorded. We explored the outcomes of SCAD patients who underwent PCI during their initial presentation. Results. PCI was performed in 75 patients, the average age was 48.9 ± 10.1 yrs, and 94.7% were women. All presented with MI; 50.7% STEMI, 49.3% NSTEMI, and 13.3% had VT/VF. PCI was successful in 34.7%, partially successful in 37.3%, and unsuccessful in 28.0%. Stents were deployed in 73.3%, 16.0% had balloon angioplasty alone, 10.7% had wiring attempts only, and 5.3% required bailout surgery. Major adverse cardiovascular event rates (MACE) were significantly higher with the PCI group in hospital (29.3% versus 2.8%, p<0.001), and at median follow-up of 3.7 yrs (58.7% versus 22.6% (p<0.001) compared to the non-PCI group. Conclusion. PCI in SCAD patients was associated with high failure rate and MACE in hospital and at long-term follow-up. These findings support the recommendation of conservative therapy as first-line management unless high-risk features are present.